2019
DOI: 10.3390/catal9121005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of Electrospun β-Ga2O3 Nanofibers via In-Situ Si Doping Using Tetraethyl Orthosilicate

Abstract: β-Ga 2 O 3 has attracted considerable attention as an alternative photocatalyst to replace conventional TiO 2 under ultraviolet-C irradiation due to its high reduction and oxidation potential. In this study, to enhance the photocatalytic activity of β-Ga 2 O 3 , nanofibers are formed via the electrospinning method, and Si atoms are subsequently doped. As the Si concentration in the β-Ga 2 O 3 nanofiber increases, the optical bandgap of the β-Ga 2 O 3 nanofibers continuously decreases from 4.5 eV (intrinsic) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…The pH value in the solution was adjusted to approximately 10 by adding an ammonium hydroxide solution (NH 4 (OH) 28 vol% in H 2 O) which was necessary to form b-Ga 2 O 3 nanostructures via a hydrothermal reaction. 26,27,31 To dope Al in the b-Ga 2 O 3 nanostructures with different concentrations, different amounts of aluminum nitrate nonahydrate (Al(NO 3 ) 3 $9H 2 O) (0.02, 0.064, 0.110, and 0.210 g for Al 0…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH value in the solution was adjusted to approximately 10 by adding an ammonium hydroxide solution (NH 4 (OH) 28 vol% in H 2 O) which was necessary to form b-Ga 2 O 3 nanostructures via a hydrothermal reaction. 26,27,31 To dope Al in the b-Ga 2 O 3 nanostructures with different concentrations, different amounts of aluminum nitrate nonahydrate (Al(NO 3 ) 3 $9H 2 O) (0.02, 0.064, 0.110, and 0.210 g for Al 0…”
Section: Methodsmentioning
confidence: 99%
“…The supersaturated mixed solution was transferred to a Teon-lined stainless-steel autoclave, thermally treated at 140 C for 10 h, and subsequently cooled down naturally to room temperature. 26,27,31 Aer the hydrothermal synthesis process, a-GaOOH nanostructures with different Al concentration were collected, washed three times with DI water, and then dried in an oven at 70 C for 6 h. It is noted that a-GaOOH nanostructures were precipitated in dissolved solutions (Ga(NO 3 ) 3 $xH 2 O) with an (NH 4 (OH)) alkali in this work, and it was reported that the a-GaOOH nanostructures were also precipitated in dissolved solutions (Ga(NO 3 ) 3 $xH 2 O) with other alkalis such as NaOH, KOH, NaHCO 3 , and Na 2 CO 3 . 32 In addition, the morphologies of the GaOOH were found to have signicantly different in terms of pH values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also seen in Raman spectroscopy data for the 800 °C samples as discussed in the section followed immediately after this. Overall, based on structural analysis, the as-deposited nanofibers are amorphous, which fully transform to crystalline β-phase Ga 2 O 3 nanofibers, which is in good agreement with the reports in the literature for Ga 2 O 3 nanofibers made by the electrospinning process. , Zhao also reported that, in order to obtain crystalline nanofibers, samples were annealed at 900 °C in air for 3 h . Similarly, Yoo et al obtained Si-doped β-Ga 2 O 3 nanofibers via the electrospinning method by thermal treatment 900 °C in air for 6 h. Thus, comparing our results with intrinsic Ga 2 O 3 nanofibers along with those reported on either intrinsic or doped Ga 2 O 3 nanofibers, we can conclusively indicate that a temperature on the order of 900-1000 °C for 2–3 h is optimum to realize crystalline β-phase Ga 2 O 3 nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…From group theory symmetry analysis, the number of expected optical vibrational modes of Ga 2 O 3 is 27, and among these vibrational modes, 15 are Raman active, while 12 are infrared active . Raman spectra of Ga 2 O 3 are classified into three regions: a high-frequency region (770–500 cm –1 ) which includes stretching and bending modes of GaO 4 tetrahedra, phonon modes in a middle frequency region (480–310 cm –1 ) due to deformation of GaO 6 octahedra, and phonon modes in a low-frequency region (below 200 cm –1 ) due to the oscillation and translation of Ga–O chains. , Figure shows the Raman spectra of as-prepared and thermally annealed samples. Corroborating with structural data, as-prepared samples (prior to heat treatment) exhibit broader peaks, indicating the amorphous nature of the nanofibers.…”
Section: Resultsmentioning
confidence: 99%